PEMBELAJARAN BERBASIS PRAKTIKUM UNTUK MENINGKATKAN HASIL BELAJAR DENGAN SOAL HOTS MATA PELAJARAN IPA - RIANA SUSANTI (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2023)
HOTS questions are one of the demands of skills in 21st century learning. These skills can be developed through practicum activities carried out in study groups both in learning activities and activities outside the classroom. HOTS (Higher Order Thinking Skill) questions are questions of higher order thinking, because they require analysis to answer them. The students of SMP Negeri 1 Mojotengah have very poor higher-order thinking skills. This can be seen when working on HOTS questions on the Final Semester Assessment (PAS) questions, their learning outcomes are low. Practicum-based learning provides an alternative to make students better understand HOTS questions. The research objective is to improve learning outcomes with HOTS questions for students through practicum-based learning. There are 2 data collection techniques, namely testing and documentation techniques. Research Results Practicum-based learning can improve learning outcomes with HOTS questions, this can be seen from the analysis of student learning outcomes, namely 83% with the criteria for class VIIIE student learning outcomes being very good and the average posttest score of 83.1. Practicum-based learning increases learning outcomes with HOTS questions. This can be seen from the hypothesis test showing t count 5.441 ? t table: 2.657 this indicates that there is a significant difference between the learning outcomes of the control class and the experimental class. Thus practicum-based learning can improve student learning outcomes with HOTS questions. ABSTRAKSoal HOTS merupakan salah satu tuntutan keterampilan dalam pembelajaran abad 21. Ketrampilan tersebut dapat dikembangkan melalui kegiatan praktikum yang dilakukan dalam kelompok belajar baik dalam kegiatan pembelajaran maupun kegiatan di luar kelas. Soal HOTS ( Higher Order Thinking Skill) merupakan soal berpikir tingkat tinggi, karena membutuhkan analisis untuk menjawabnya. Peserta didik SMP negeri 1 Mojotengah kemampuan dalam berpikir tingkat tinggi masih sangat kurang hal ini dapat dilihat saat mengerjakan soal HOTS pada soal Penilaian Akhir Semester ( PAS) hasil belajarnya rendah. Dengan pembelajaran berbasis praktikum memberikan alternatif untuk membuat siswa lebih memahami soal HOTS. Tujuan penelitian untuk meningkatkan hasil belajar dengan soal HOTS bagi siswa melalui pembelajaran berbasis praktikum. Teknik pengumpulan data ada 2 yaitu teknik tes dan dokumentasi. Hasil Penelitian Pembelajarn berbasis praktikum dapat meningkatkan hasil belajar dengan soal HOTS, hal ini terlihat dari analisis hasil belajar siswa yaitu 83% dengan kriteria hasil belajar siswa kelas VIIIE baik sekali dan nilai rata rata postests 83,1. Pembelajarn berbasis praktikum terjadi peningkatan hasil belajar dengan soal HOTS. Hal ini terlihat dari uji hipotesis menunjukkan t hitung 5,441 ? t tabel : 2,657 ini menunjukkan bahwa ada perbedaan yang signifikan antara hasil belajar kelas kontrol dengan kelas eksperimen. Dengan demikian Pembelajaran berbasis praktikum dapat meningkatkan hasil belajar siswa dengan soal HOTS.